2023
DOI: 10.31004/obsesi.v7i1.3360
|View full text |Cite
|
Sign up to set email alerts
|

Digital-Based Portfolio Assessment Competence of Early Childhood Educators

Abstract: In today's era of digital-based learning management, educators must have knowledge and skills in the use of digital technology in teaching and learning activities. This study aims to analyze data on the competence of digital-based portfolio assessment of Early Childhood Care and Education (ECCE) teachers who teach at Kindergarten and Playgroup in the city of Bandung. The research method used was descriptive with a qualitative approach. The research informants included 14 teachers, 3 principals, and 1 vice prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…Self-efficacy refers to the belief that a person can plan, carry out tasks, achieve goals, produce things, and implement plans to master certain talents. Apart from that, there are also several other areas of research that need to be improved by kindergarten teachers, including digital-based portfolio assessment competencies (Maciej Serda, Becker et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy refers to the belief that a person can plan, carry out tasks, achieve goals, produce things, and implement plans to master certain talents. Apart from that, there are also several other areas of research that need to be improved by kindergarten teachers, including digital-based portfolio assessment competencies (Maciej Serda, Becker et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the utilization of digital platforms and support services for teacher learning is well-supported by research. The principals' use of platforms like "Merdeka Belajar" and support centers for information about the Independent Curriculum aligns with the growing trend of leveraging technology to enhance teacher learning and collaboration (Marsegi et al, 2023;Musa et al, 2022;Nurhayati et al, 2023;Nurmalia et al, 2022;Suharyat et al, 2022;Winarti et al, 2022;Zheltukhina et.al., 2023). The strategies employed by the ECCE principals in Kecamatan Arcamanik not only reflect a comprehensive approach to enhancing teacher competence but also align well with current research on effective teacher development practices such as Nurhayati (2020), Wesołowska (2018), and Rosero et.al (2018) which found that teacher competence can be enhanced through the right kind of workshop.…”
Section: Implementation Of the Independent Curriculum (Kurikulum Merd...mentioning
confidence: 98%
“…Asesmen terhadap hasil belajar peserta didik yang meliputi aspek karakter, aspek pengetahuan (kognitif), aspek sikap (afektif), dan aspek keterampilan (psikomotorik) yang diwujudkan dalam kebiasaan berfikir dan bertindak. Asesmen Portofolio merupakan salah satu jenis penilaian yang digunakan dalam ABK dan memiliki makna optimal dalam melihat ketercapaian kompetensi belajar peserta didik (Kristiawan et al, 2013;Julaeha & Amalia, 2016;Karimah & Wahyu, 2019;Kholidiyah et al, 2022;Marsegi et al, 2023).…”
Section: Pendahuluanunclassified